PENGARUH MOTIVASI, KOMITMEN, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI RUMAH SAKIT DAERAH MADANI PROVINSI SULAWESI TENGAH - Saifudin, Saifudin (Katalogis, 2017)
This research intends to define and analyze the simultaneous and partial influence of motivation, commitment, work environment, and job stress on civil servantsâ€™ performance in Madani Hospital of Central Sulawesi Province. It involves 218 officials as respondents and uses descriptive approach with multiple regressions analysis. The results find that motivation, commitment, work environment, and job stress simultaneously and partially have significant influences on civil servantsâ€™ performance in Madani Hosptila of Central Sulawesi Province.Â